1987
DOI: 10.1017/s0022215100103226
|View full text |Cite
|
Sign up to set email alerts
|

Serum enzymes in head and neck cancer III

Abstract: Serum adenosine deaminase (ADA) levels were estimated in a group of 40 patients with head and neck cancer. The mean value was significantly higher in patients compared to controls. The increase was higher in cases of ulcerative growths than of proliferative growths, and activity was increased with advancement in the stage of the cancer. After radiotherapy, a gradual and significant decrease in serum ADA activity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
1
10
1
3
Order By: Relevance
“…There are no markers of tumor growth in our study, but if the cytokines pattern observed is taken in account, ADA reduction may have been an attempt to preserve the extracellular adenosine level. However, a previous study reported that increased ADA activity in serum may indicate malignancy [61]. Diverging from our findings, researchers reported an increase in total ADA activity in women breast cancer [62].…”
Section: Discussionsupporting
confidence: 66%
“…There are no markers of tumor growth in our study, but if the cytokines pattern observed is taken in account, ADA reduction may have been an attempt to preserve the extracellular adenosine level. However, a previous study reported that increased ADA activity in serum may indicate malignancy [61]. Diverging from our findings, researchers reported an increase in total ADA activity in women breast cancer [62].…”
Section: Discussionsupporting
confidence: 66%
“…Serum ADA levels were found to be increased in laryngeal cancer [9] , head and neck cancer [10] , breast cancer [11] and lung cancer [12] . The levels of ADA decreased after surgery or radiotherapy which was thought to be due the inhibition of leakage of the enzyme from the primary tumor or from metastases [10,12] .…”
Section: Discussionmentioning
confidence: 99%
“…Mesane ve akciğer kanseri üzerine yapılan çalışmalarda da benzer sonuçlar elde edilmiştir (19,20). Baş-boyun kanserlerine ilişkin bir araştırmada da serumda, kontrol grubuna göre yüksek ADA düzeyleri bulunmuş ve radyoterapi sonrasında enzim düzeylerinde düşüş olduğu görülmüştür (21). Bu konuda yapılan son bir çalışmada da, larenks kanserli hastalarda cerrahi eksizyon öncesi ve sonrasında serum ADA aktiviteleri ölçülmüş, hastalarda enzim aktivitesi yüksek bulunurken, pre ve postoperatif fark gösterilememiştir (22).…”
Section: Discussionunclassified
“…Bu konuda yapılan daha önceki çalışmalarda olduğu gibi (21,22) biz de ADA düzeylerini hasta grubunda hem toplam olarak hem de her bir evre için, kontrole göre yüksek bulduk ve bu yükselmenin tümör küt-lesi ve yayılımıyla bağlantılı olarak hastalık evresiyle paralel olduğunu da gördük (Tablo 1 ve 2). Aynı bulgu serum CD aktivitesi için de geçerlidir.…”
Section: Discussionunclassified
See 1 more Smart Citation